The Engine 2 seven-day rescue diet : eat plants, lose weight, save your health - Esselstyn, Rip; Esselstyn, Jane (Grand Central Life & Style, 2016)
A follow-up to "The Engine 2 Diet" outlines a seven-day vegetarian program designed for rapid weight loss and lower cholesterol, triglyceride, and blood-pressure counts.